The temporal relationship between mitochondrial quality and renal tissue recovery following ischemia-reperfusion injury - Priyanka N. Prem; Harish Swaminathan; Gino A. Kurian (Heliyon)
Background: Growing evidence indicates that disruptions in mitochondrial quality management contribute to the development of acute kidney injury (AKI), incomplete or maladaptive kidney repair, and chronic kidney disease. However, the temporal dynamics of mitochondrial quality control alterations in relation to renal injury and its recovery remain poorly understood and are addressed in this manuscript. Method: ology: Male Wistar rats (n = 60) were subjected to varying durations of ischemia and reperfusion. Ischemia was instigated by clamping both renal arteries and for reperfusion, the clamps were removed to restore the blood flow. Renal injury, physiological function, mitochondrial assessment, and cellular mediators were analyzed. Results: Prolonging ischemia duration reduces bioenergetic function while disrupting the balance of mitochondrial fusion, fission, and mitophagy at the gene expression level while maintaining intact mitochondrial copy number. However, reperfusing a kidney after 45 min of ischemia with varying reperfusion times exacerbates mitochondrial dysfunction and significantly decreases mitochondrial copy number. These declines are particularly evident at 24 h of reperfusion, with some parameters improving by 7 days of reperfusion. Despite these improvements, 7 days of reperfusion did not correlate with renal injury indicators (CrCl- 0.46 ± 0.01, BUN-86.29 ± 4.9, Cr-1.75 ± 0.16) following 45 min of ischemia. Conversely, 15 min of ischemia followed by 7 days of reperfusion restored mitochondrial quality and renal function (CrCl- 7.33 ± 0.59, BUN-43.6 ± 3.16, Cr-0.93 ± 0.14). Conclusion: The above findings emphasize that mitochondrial quality control alters with the extent of ischemia and subsequent reperfusion time, impacting not only mitochondrial copy number but also the resilience of mitochondria during tissue repair.